MANTLE HYDROCARBONS: ABIOTIC OR BIOTIC? - Sugisaki R.; Mimura K. (My University, 1994)
Analyses of 227 rocks from fifty localities throughout the world showed that mantle derived rocks such as tectonized peridotites in ophiolite sequences (tectonites) arid peridotite xenoliths in alkali basalts contain heavier hydrocarbons (n-alkanes), whereas igneous rocks produced by magmas such as gabbro arid granite lack them. The occurrence of hydrocarbons indicates that they were not derived either from laboratory contamination or from held contamination; these compounds found in the mantle-derived rocks are called here "mantle hydrocarbons." The existence of hydrocarbons correlates with petrogenesis. For example, peridotite cumulates produced by magmatic differentiation lack hydrocarbons whereas peridotite xenoliths derived from the mantle contain them. Gas chromatographic-mass spectrometric records of the mantle hydrocarbons resemble those of aliphatics in meteorites and in petroleum. Features of the hydrocarbons are that (a) the mantle hydrocarbons reside mainly along grain boundaries and in fluid inclusions of minerals; (b) heavier isoprenoids such as pristane and phytane are present; and (c) delta 13C of the mantle hydrocarbons is uniform (about -27%). Possible origins for the mantle hydrocarbons are as follows. (1) They were in organically synthesized by Fischer-Tropsch type reaction in the mantle. (2) They were delivered by meteorites and comets to the early Earth. (3) They were recycled by subduction. The mantle hydrocarbons in the cases of (1) and (2) are abiogenic and those in (3) are mainly biogenic. It appears that hydrocarbons may survive high pressures and temperatures in the mantle, but they are decomposed into lighter hydrocarbon gases such as CH4 at lower pressures when magmas intrude into the crust; consequently, peridotite cumulates do not contain heavier hydrocarbons but possess hydrocarbon gases up to C4H10.